2021
DOI: 10.1002/elan.202100083
|View full text |Cite
|
Sign up to set email alerts
|

Sweat Based‐multiplexed Detection of NPY‐Cortisol for Disease Diagnostics and Stress Management

Abstract: Cortisol and Neuropeptide Y(NPY) are chronobiological markers of stress. Non‐invasive tracking of these two biomolecules can provide great insight into an individual's physiological and neurological wellbeing. This work presents the development of a platform that tracks the two biomarkers in ultra‐low volumes (5 μL) of sweat using electrochemical impedance spectroscopy (EIS). The sensing platform was able to detect both molecules in their relevant physiological ranges (8.16–141.7 ng/mL and 50–200 pg/mL respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…While the etiology and pathways of stress modulation are still under active research being able to monitor simultaneously, the modulation of these stress biomarkers concerning different stress conditions can prove helpful, especially for chronic stress, which requires monitoring. While various research groups have looked into the combinatorial detection of cortisol and NPY toward stress (Antonijevic et al, 2000; Held et al, 2006; Kapritsou et al, 2017; Morgan et al, 2001, 2002; Seedat et al, 2003; Westrin et al, 1999), to the best of our knowledge, there has not been any reported research to the best of our knowledge that has carried out these experiments in sweat apart from Churcher, Greyling, et al (2022); Churcher, Upasham, et al (2022).…”
Section: Emerging Perspective Of Application Of Nanotechnology Based ...mentioning
confidence: 97%
See 2 more Smart Citations
“…While the etiology and pathways of stress modulation are still under active research being able to monitor simultaneously, the modulation of these stress biomarkers concerning different stress conditions can prove helpful, especially for chronic stress, which requires monitoring. While various research groups have looked into the combinatorial detection of cortisol and NPY toward stress (Antonijevic et al, 2000; Held et al, 2006; Kapritsou et al, 2017; Morgan et al, 2001, 2002; Seedat et al, 2003; Westrin et al, 1999), to the best of our knowledge, there has not been any reported research to the best of our knowledge that has carried out these experiments in sweat apart from Churcher, Greyling, et al (2022); Churcher, Upasham, et al (2022).…”
Section: Emerging Perspective Of Application Of Nanotechnology Based ...mentioning
confidence: 97%
“…In Churcher, Upasham, et al (2022), the authors have demonstrated a platform capable of simultaneously detecting cortisol and NPY using an antibody affinity‐based immunoassay platform in synthetic sweat (with different pH.) and in pooled human sweat.…”
Section: Emerging Perspective Of Application Of Nanotechnology Based ...mentioning
confidence: 99%
See 1 more Smart Citation
“…SPR has also been used to characterize the immobilization of an affinity reagent, rather than testing binding to the target itself. Churcher, Upasham, and coworkers utilized SPR for the real-time monitoring of antibodies onto a Protein A functionalized surface, to verify they could attach the molecule of interest to a biosensor that relied on a different method of detection [ 220 , 221 , 222 ]. While many papers use SPR to supplement other investigations, some studies focused on developing biosensors based entirely on the technique of LSPR itself [ 34 , 45 ].…”
Section: Beyond Simple Kinetics: the Versatility Of Opensprmentioning
confidence: 99%
“…However, measurements were only possible as low as 20 nM (4704 pg/mL), which is much higher than needed for brain measurements. Churcher et al reported a detection limit of NPY of 10 and 50 pg/mL in sweat using antibodies and larger electrodes. This is a significant advance in the field, with the main issue being the intrinsic disadvantages of antibodies that are not stable for long-term use and the fact that these electrodes cannot be used in the brain due to their size.…”
mentioning
confidence: 99%